The influence of capital expenditures and original regional income (pad) on economic growth in central maluku regency - Latupapua, Dalfin Rinhard; Nikijuluw, Jeanee B (Central Research Institute for Agriculture (CeRIA), 2024)
This writing aims to determine the influence of Capital Expenditures and GRDP on economic growth in the Central Maluku Regency area. Using time series data for the 2013-2022 period obtained from BPS Central Maluku Regency, the data was then processed using the Eview program with a multiple linear regression equation model and the mathematical derivative equation Ln_Y = α + β1 Ln_X1 + β2 Ln_X2 + ε. Then transformed based on the regression results as follows: Y = 10.492 + 0.028 LN_X1 + 0.222 LN_X2 + ε This equation is then explained that, if all the independent variables which include the Capital Expenditure variable (LN_X1), the Original Regional Income variable (LN_X2) have a value of 0 percent or have not changed, then the Economic Growth value is 10.492. The regression coefficient value for the Capital Expenditure variable (LN_X1) has a positive value of 0.028. This shows that if Capital Expenditures increase by 1%, then Economic Growth will increase by 0.028 or 2.8%. Meanwhile, the regression coefficient value for the Regional Original Income variable (LN_X2) has a positive value of 0.222. This shows that if Original Regional Income experiences an increase of 1%, then Economic Growth will increase by 0.222 or 22.2% assuming other independent variables are considered constant. The results of the partial test (t test) of the Capital Expenditure variable (X1) have no significant effect on Economic Growth. The variable Original Regional Income (X2) partially has a significant effect on economic growth. Meanwhile, the R square value is 0.677987 or 67.79%, which explains that simultaneously the capital expenditure and PAd variables have a significant effect on economic growth by 67% while the remaining 32.21% is influenced by other factors outside the factors studied